2017
DOI: 10.1063/1.4996918
|View full text |Cite
|
Sign up to set email alerts
|

Low-loss saturable absorbers based on tapered fibers embedded in carbon nanotube/polymer composites

Abstract: The emergence of low-dimensional materials has opened new opportunities in the fabrication of compact nonlinear photonic devices. Single-walled carbon nanotubes were among the first of those materials to attract the attention of the photonics community owing to their high third order susceptibility, broadband operation, and ultrafast response. Saturable absorption, in particular, has become a widespread application for nanotubes in the mode-locking of a fiber laser where they are used as nonlinear passive ampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Recently, researchers have reported that the two kinds of pulses, harmonic soliton molecules and rectangular noise-like pulses, can be coexisted in a fiber laser (Huang et al, 2016). In addition, different real saturable absorbers (SAs) can also be excellent composed for the generation of multiple pulses in the fiber laser cavity (Martinez et al, 2017; Lai et al, 2018). Other researchers reported that bound soliton and harmonic mode-locking soliton could be coexisted in an ultrafast fiber laser by MoS 2 SA for a photonic device (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers have reported that the two kinds of pulses, harmonic soliton molecules and rectangular noise-like pulses, can be coexisted in a fiber laser (Huang et al, 2016). In addition, different real saturable absorbers (SAs) can also be excellent composed for the generation of multiple pulses in the fiber laser cavity (Martinez et al, 2017; Lai et al, 2018). Other researchers reported that bound soliton and harmonic mode-locking soliton could be coexisted in an ultrafast fiber laser by MoS 2 SA for a photonic device (Liu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such interaction types originate from direct interaction between CNT and transmission light; however, high-power tolerance may be a limit. Other approach based on evanescent filed can be a candidate and SWNTs can be coated on a D-shaped fiber [171,172], microfiber [173,174], or injected into microslot [175,176], photonic crystal fiber [177] and hollow core fiber [178]. Recently, the development of SWNT SAs pays more attention on power handing, environmental stability and more outstanding SA characteristics including sol-gel method and glass doping [179,180].…”
Section: Development Of Cnt Sasmentioning
confidence: 99%
“…Low-dimensional materials have attracted increasing attention in nonlinear optics due to their remarkable optoelectronic properties. For instance, one-dimensional carbon nanotubes (CNTs) and two-dimensional (2D) graphene were found to possess ultrafast carrier dynamics and high third-order nonlinear susceptibility [1][2][3][4][5][6][7][8][9]. Over the past decade, 2D materials have been widely reported in nonlinear optics, ultrafast photonics, and other fields due to their energy band structure and splendid crystals [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%